2016
DOI: 10.1037/pas0000276
|View full text |Cite
|
Sign up to set email alerts
|

Multifacet assessment of capability for suicide: Development and prospective validation of the Acquired Capability With Rehearsal for Suicide Scale.

Abstract: The interpersonal theory of suicide proposes that acquired capability facilitates transformation of suicidal desire into lethal self-destructive behavior (Joiner, 2005). A new measure, the Acquired Capability With Rehearsal for Suicide Scale (ACWRSS), was devised to capture the key facets of acquired capability-pain tolerance and fearlessness of death-while also incorporating deliberate and active means to increase preparedness for suicide. The factor structure of the ACWRSS was tested using confirmatory facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
73
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 64 publications
10
73
0
3
Order By: Relevance
“…To meet criteria for PTSD based on DSM-5, individuals need to have at least one threshold criterion B symptom (re-experiencing), one threshold criterion C symptom (avoidance), two criterion D symptoms (negative cognitions and mood), and two criterion E symptoms (reactivity and arousal), as well as duration longer than one month and functional impairment present (score ≥ 1). CAPS has been used in both civilian and veteran populations and shown good to excellent reliability and validity across multiple studies (Blake et al, 1995; Bovin et al, 2016; Pupo et al, 2011; Weathers, Keane, & Davidson, 2001). Interrater reliability (IRR) was calculated on a subsample of participants (6.0%, n  = 12) and showed good IRR for diagnosis of PTSD ( k =  0.83).…”
Section: Methodsmentioning
confidence: 99%
“…To meet criteria for PTSD based on DSM-5, individuals need to have at least one threshold criterion B symptom (re-experiencing), one threshold criterion C symptom (avoidance), two criterion D symptoms (negative cognitions and mood), and two criterion E symptoms (reactivity and arousal), as well as duration longer than one month and functional impairment present (score ≥ 1). CAPS has been used in both civilian and veteran populations and shown good to excellent reliability and validity across multiple studies (Blake et al, 1995; Bovin et al, 2016; Pupo et al, 2011; Weathers, Keane, & Davidson, 2001). Interrater reliability (IRR) was calculated on a subsample of participants (6.0%, n  = 12) and showed good IRR for diagnosis of PTSD ( k =  0.83).…”
Section: Methodsmentioning
confidence: 99%
“…While long‐term CS has been described theoretically and several cross‐sectional studies have supported its associations with suicide attempts within the framework of the ITS (Glaesmer et al., ; Ma, Batterham, Calear, & Han, ), the IMV (Dhingra, Boduszek, & O'Connor, ), and the 3‐ST (Dhingra, Klonsky, & Tapola, ), empirical evidence from prospective studies about its development and its predictive value for suicidal behavior is rare (Ma et al., ; George, Page, Hooke, & Stritzke, ; May & Victor, ).…”
Section: Capability For Suicidementioning
confidence: 99%
“…Moreover, George et al. () have evaluated the sensitivity of the CS facets to change after treatment in a prospective study in clinical inpatients demonstrating that the two facets differ in terms of stability: While fearlessness about death decreased after inpatient treatment (psychiatric acute care), pain tolerance did not change significantly. Although this provides first evidence that CS is subject to change over time (i.e., casting further doubt on the initially assumed static nature of the construct and supporting the assumption by Smith and Cukrowicz that there is a short‐term component of CS that may change in rather short periods), neither its temporal dynamics nor factors contributing to momentary shifts have been studied to date (Anestis et al., ; May & Victor, ).…”
Section: Capability For Suicidementioning
confidence: 99%
See 1 more Smart Citation
“…In an examination of the role of emotion regulation and self‐injury on suicidal behavior, Heffer and Willoughby () found that emotion dysregulation predicted lower ACS among undergraduates at yearly measurements, controlling for earlier levels of ACS. A scale was recently developed to measure the facets of ACS as well as preparations for suicide; initial testing of this scale in an inpatient sample showed that mean levels of FAD by suicide and preparedness for suicide reduced between admission and discharge (George, Page, Hooke, & Stritzke, ). Both of these studies provide convergent evidence that ACS may not increase monotonically, as originally predicted, but neither examined person‐level changes in ACS over time.…”
Section: The Acquired Capability For Suicidementioning
confidence: 99%